Impact of frontline demonstration (FLD) and trainings on knowledge and adoption level of mustard growers of Western Rajasthan: FLD AND TRAINING FOR MUSTARD PRODUCERS - M L MEHRIYA; R L BHARDWAJ; M KUMAR; I SINGH; J R VERMA (Journal of Oilseeds Research, 2020)
Agricultural Research Station, Mandor organized five, two days on-campus trainings, 100 frontline demonstrations (FLDs) and five field days for selected 480 mustard growers during 2016-17. One hundred farmers comprising of 20 from each block i.e. Nagaur, Maulasar, Jalore, Barmer and Jodhpur were selected purposively for the study. It was observed that the farmers adopted new high yielding variety, seed treatment, crop rotation, integrated nutrient management, plant protection measures and used recommended seed rate after undergoing the trainings. The results also revealed that due to enhanced knowledge and adoption of scientific practices, the yield of mustard increased from 11.1 to 29.2% over the yield obtained under farmer’s practices during the year 2016-17. The extension gap (167-416 kg/ha), technological gap (84-967 kg/ha) and technology index (4.20-42.04%) exhibited the feasibility of demonstrated technology. The farmers under medium and higher level of knowledge groups increased from 20 to 52% and from 15 to 31%, respectively. Besides, the adoption level increased from 18 to 63% and 9 to 17% in medium level and high level, respectively. Further, farmers under low level of adoption declined from 73 to 20%. Thus, this study suggests the need of conducting intensive trainings and FLDs to educate the mustard growers for achieving higher production of mustard in the western districts of Rajasthan.